An Empirical Study of Key Strategy Factors of Diversity and Inclusion and its Impact on Employees performance in ITES Sector (International Journal of Scientific Research in Science and Technology, 2024)
In this research study the researcher indentify the factors of key strategies of diversity and inclusion at the workplace which significantly enhance the organizational activities such as Leadership Commitment, Training and Education, Inclusive, Policies, Flexible Work Arrangements, Regular Feedback, Diverse Recruitment, Employee Resource Group, Accountability and Measurement. The researcher used the 400 data sample based on the structured questionnaire from the various ITES sectors at different level of employees. This research study is designed with the help of primary and secondary data which are collected through the different research articles and structured questionnaires. For data analysis and interpretation researcher used the SPSS software and Chi-square hypothesis testing tool to test the hypothesis at 0.05 significant levels. The statistical analysis shows that Strongly Disagree 3.8% ,Disagree 11.3% , Neutral 8.8%, Agree 33.0%, Strongly Agree 41.5% are supported to the key strategies for diversity and inclusion at the workplace which significantly enhance the organizational activities. The probability of statistics P-Value is 0.000 which is less than 0.05 significant levels, so the null hypothesis is rejected and result is significant. At this level the researcher concluded that attributes of key strategies for diversity and inclusion at the workplace which significantly enhance the organizational activities.
Keywords: diversity; inclusion; ITES; Equality; Employees Performance